Hidden facts. The modern family and its problems - Katarzyna Miłek (Kultura i Wychowanie)
This article is an attempt to explain the transformation of the contemporary family. It considers how it is changing and explores why we encounter many breakdowns of this social group. The author contends that breakdowns are often the consequence of external factors, i.e., mass media (in particular), which disturb the proper functioning of the family. Referring to numerous definitions of the family, the article lists the fundamental functions that are the most important in our life.